Ecological Governance of Rubber in Xishuangbanna, China - Janet C Sturgeon; Nicholas K Menzies; Noah Schillo (Conservation & Society, 2014)
In recent years, the Xishuangbanna Tropical Botanic Garden (XTBG) and the Xishuangbanna prefecture government have woken up to the environmental threat that extensive monoculture rubber cultivation poses in this tropical site in southern Yunnan. In response, XTBG has become a centre of knowledge production on how to restore some ethnic minority farmers′ rubber fields to natural forest. As is common globally, the plan relies on mainstream ecology and leaves out farmers′ experience and opinions. Curiously, in the 1980s and 1990s XTBG was a centre of human ecology research on farmers′ knowledge about managing ecosystems and protecting biodiversity. This paper traces the transformation in the values, actors, institutional configurations, and epistemic communities that enabled farmers′ experiences to be central to knowledge production and inscription across surrounding landscapes in the 1980s and 1990s, only to be disparaged and ignored in the production of knowledge and landscapes in the 2000s. Farmers who once taught XTBG scientists the names of species and how to survive on them during the Cultural Revolution are now excluded from determining how to restore those same species to the hills around them. Our analysis suggests possible pathways for ecological knowledge to be generated as well as lost.